Удосконалення кримінального процесуального законодавства України щодо підслідності органів досудового розслідування - Микола Погорецький; Волкотруб, С. Г. (Видавнича компанія «АЛЕРТА», 2017)
У статті висвітлюються проблемні питання, пов’язані з застосування норм чинного кримінального процесуального законодавства України, що регламентують інститут підслідності кримінальних проваджень, а також надаються науково-обґрунтовані пропозиції щодо їх вирішення.

The article is devoted to issues of using current criminal procedure law of Ukraine regulating the jurisdiction institute of criminal proceedings and providing scientific and reasonable propositions to solve them. It is proved that during the improvement of the current legislation of Ukraine should abandon the practice of fixing criminal procedural rules in other legislation, such as the provisions are clearly contrary to part 3 of the Art. 9 of the CPC of Ukraine and create conditions for disputes in criminal procedural activities. The article took note that in the current criminal procedural legislation of Ukraine and practice of its using it is created the situation when during the preliminary investigation, the participants of criminal proceedings deprived of the opportunity to appeal to the investigating judge unjustified procedural decisions on definition of jurisdiction, which prevents operational elimination of violations law and creates conditions for the recognition of evidence inadmissible on the results of the trial. It is proposed to make amendments to part 4 of the Art. 214 of the CPC of Ukraine the following provision: «If there is information indicating non jurisdiction of the criminal proceedings to the pre-trial investigation, which has been accepted and registered Crime Incident Report or report of a crime, the investigator, the other officer make a petition to the prosecutor request for determining jurisdiction, which must be solvable immediately, but not later than 24 hours. The preliminary investigation in the criminal proceedings, which is not jurisdiction of the body, it is possible only during the initial work concerning the urgent investigative (detective) action at the end of which all the materials of the criminal proceedings are immediately transmitted investigative jurisdiction».
Improvement of the criminal procedure legislation of investigative jurisdiction of the preliminary investigation bodies
Keywords: підслідність; слідчий; прокурор; доказ; investigative jurisdiction; investigator; public procurator; evidence